The Hospitallers: From Land to Sea—An Examination of the Hospitallers' Naval Activities in the Twelfth and Thirteenth Centuries. (May 2019) - Bronstein, Judith
The purpose of this article is to examine the regional and inter-Mediterranean deployment of the Hospitallers in the twelfth and thirteenth centuries and their use of port towns along the Mediterranean shores. These ports were essential for the communication between the Order's headquarters in Jerusalem, and later in Acre, and its commanderies, for the shipment of goods and manpower, and for the Order's involvement in regional and trans-Mediterranean trade. The article also examines changes made in the Order's organisational structure, which resulted from the increasing dependence of the Hospitallers on a fleet. These are significant changes; they would eventually create the tools that enabled the Hospitallers to become a 'maritime' orientated Military Order, taking a leading role in the defence of the Eastern Mediterranean.